Convection, Terrestrial Recycling and Oceanic Moisture Regulate the Isotopic Composition of Precipitation at Srinagar, Kashmir. Issue 7 (6th April 2021) - Dar, Shaakir Shabir; Ghosh, Prosenjit; Hillaire‐Marcel, Claude
Abstract: The moisture transport and precipitation in the western Himalayas is an interplay of two atmospheric systems: Western Disturbances (WDs) and Indian Summer Monsoon (ISM). WDs primarily transport moisture from the Mediterranean Sea and the Atlantic Ocean, while ISM transports moisture from the Arabian Sea and the Bay of Bengal. Local moisture sources also contribute to the regional precipitation budget. The moisture sources can be distinguished by measuring dual isotopic signatures in precipitation. Oxygen and hydrogen isotopic ratios measured in daily precipitation samples collected at Srinagar, Kashmir from March 2015–April 2017, allowed delineating the role of factors like large‐scale moisture transport processes, and local meteorological factors such as temperature, precipitation amount and relative humidity on the precipitation isotope ratios and its effect on the meteoric water line parameters. Isotopic data were further used to estimate the percentage contributions of distinct moisture sources across different seasons and validation of an isotope enabled general circulation model (iEGCM). We found that the time integrated, large‐scale convection over several days, constitutes a major factor governing the isotopic composition of precipitation, while the role of local meteorological parameters is minimal. A box model to simulate the moisture transport and estimate the oceanic versus terrestrially recycled moisture sources to the regional precipitation reveals Arabian sea to be the key moisture source. Finally, on comparing the observed isotopic composition with iEGCM simulation, discrepancies are noted. Results from the present study will enable improving the interpretation of regional paleo‐climate data derived from various proxy records. Plain Language Summary: Mainland India receives precipitation mainly during summer (commonly known as the Indian Summer Monsoon) whereas, further inland, toward the Western Himalayas the precipitation is mainly received during winter (commonly known as the Western Disturbances). Measurements of oxygen and hydrogen isotopes in atmospheric and terrestrial water are cornerstones in paleoclimate and modern hydrological studies and give an indication of the presence and magnitude of key hydrological and atmospheric processes. Observations on the isotopic composition of precipitation over the Western Himalayas are poor, limiting our understanding of the precipitation forming mechanisms and hence, interpretations of paleo‐climate proxies. In this study, we found that the local meteorological factors exert a minor influence but time integrated large‐scale convection over several days majorly governs the precipitation isotopic composition. By developing an atmospheric transport model, it is revealed that Arabian sea as chief moisture source to precipitation in the Western Himalayas. Furthermore, we found deficiencies in one of the isotope enabled global climate model to predict the isotopic composition of precipitation in the Western Himalayas. Key Points: Mid‐westerly and monsoonal precipitation in the Western Himalayas has distinct oxygen and hydrogen isotopic signatures Time integrated convection chiefly governs the precipitation isotopic composition and the role of local meteorological factors is minimal Arabian Sea is a key moisture source to precipitation in the Western Himalayas